Good extrusion foaming performance of long‐chain branched PET induced by its enhanced crystallization property. Issue 41 (28th March 2020) - Yao, Shun; Guo, Tianhao; Liu, Tao; Xi, Zhenhao; Xu, Zhimei; Zhao, Ling
Abstract: Poly(ethylene terephthalate) (PET) was modified by regulating different contents of branching agent epoxy‐based multifunctional oligomer and chain extender pyromellitic dianhydride in reactive extrusion process. The modified PET with better long‐chain branched (LCB) structure boosted its rheological properties, and its enhancement of melt viscoelasticity resulted in excellent foamability in molten‐state foaming process using supercritical CO2 as blowing agent. More importantly, the branched structures acted as crystal sites to accelerate the crystallization kinetic of LCB PET whether under atmospheric pressure or high‐pressure CO2 . The shear and elongation flow inside die further quickly induced the crystallization of LCB PET. The rapidly generated fine crystals could both introduce heterogeneous cell nucleation and suppress CO2 escape, so the cell morphology of LCB PET in continuous extrusion foaming process exhibited a three‐fold increase in cell density and smaller uniform cell size with respect to those of other foam‐grade PET with long‐chain structure. Abstract :